EVALUATION OF QUALITY OF LIFE IF SPINAL CORD INJURY PATIENT AFER BASKETBALL ON WHEELS (Fiep Bulletin - online, 2012)
The practice of adapted motor activity increased significantly in recent years in Brazil, thus enabling individuals with any physical disability of character are able to do it. The spinal cord injuries are more frequent in Brazil, mainly due to increased urban violence This study aims to assess the effects of practice on quality of life of this population. This is a case study of longitudinal, comparative type cause / effect. The study was approved by the Ethics Committee of Assisi School Gurgacz - Cascavel - PR. The activities took place in the gym Gurgacz Assisi Foundation, the team was composed of academics and physical therapy physical education. Study participants were individuals diagnosed with spinal cord injury treated at the rehabilitation center of FAG in Cascavel - PR. As evaluation criterion we applied the generic questionnaire on quality of life SF-36. Comprised of 36 questions, which are evaluated eight components: physical functioning Physical Appearance Pain General Health,Vitality, Social Aspect, emotional and Mental Health presents a final score from 0 to 100, where zero corresponds to the worst overall health status and 100 the best health After analyzing the results, it is correct say that this sport can contribute to the improvement of certain aspects of quality of life of these individuals. The results of this study have revealed that the practice of basketball on wheels in this population, provided physical and functional benefits, helping to improve the emotional state and therefore the quality of life of individuals
Keywords: Motor Activity; adapted-cord injury; Quality of life.